Pengaruh Cara Dehidrasi Terhadap Karakteristik Daun Leilem (Clerodendrum minahassae Teijsm. & Binn) - Rombelayuk, Reniaty; Sumual, Maria Fransisca; Lalujan, Lana Elisabeth (Jurnal Teknologi Pertanian (Agricultural Technology Journal), 2024)
The purpose of this study is to obtain a dehydration method that can preserve the characteristics of fresh leilem leaves. The method used in this study was a Complete Randomized Design (CRD) with 4 treatments i.e; A1 (Sunlight ±31-500C), A2 (Chiller ±4-80C), A3 (room temperature ±26-300C), and A4 (Oven 600C). Each treatment is repeated 3 times. Further research results are processed using ANOVA, if there is significount influence, it is continued with a 5% BNT test. The results showed that influence of various dehydration methods on color, water content, chlorophyll, vitamin C, and rehydration of leilem leaf. Dehydration using sunlight has an L* value of 26.63, 4,49% moisture content, 31.961 mg /L total chlorophyll, 0.027ppm vitamin C, and the rehydration ratio of 2.21. Leilem leaves dehydrated using Chiller have an L* value of 29.70, 12,60% moisture content, 45.792 mg/L total chlorophyll, 0.050 ppm vitamin C, and the rehydration ratio of 2.32. In the leilem leaf dehydration method room temperature  has L* 28.67 strands, 5,54% moisture content, 41.281 mg/L total chlorophyll, 0.034 ppm vitamin C, and the rehydration ratio of 1.81. Leilem leaf dehydration using an oven has an L* value of 22.93, 3,05% moisture content, 42,132 mg/L total chlorophyll, 0.033 ppm vitamin C, and the rehydration ratio of 1.85. The best method dehydration of leilem leaves is under chiling temperature 4-80C in the chiller .The physicochemical properties of leilem leaves produced are green, showing the stability of chlorophyll pigment and has the highest water absorption of rehydration ratio.